Islamic Financial Literacy and Financial Behavior: The Case of Muhammadiyah Community in Medan City - Ade Gunawan; Asmuni Asmuni; Saparuddin Siregar (Journal of Accounting and Investment, 2021)
Research aims: This study aims to determine and analyze the level of financial behavior, the level of Muhammadiyah community’s Islamic financial literacy in Medan City, and the effect of Islamic financial literacy on financial behavior.Design/Methodology/Approach: This research is descriptive quantitative using primary data through questionnaire. The research sample was 200 members of the Muhammadiyah organization in Medan City. The data analysis technique employed confirmatory factor analysis and structural equation modeling utilizing AMOS.Research findings: The research confirmed that the level of Islamic financial knowledge among the Muhammadiyah community in Medan City was low, 60.56%. In contrast to Islamic finance knowledge, the financial behavior of the Muhammadiyah community in Medan City was classified as good; 69.01% of the Muhammadiyah community showed relatively good financial behavior. These two things make the level of Islamic financial literacy among Muhammadiyah residents in Medan City classified as less literate. This shows that in everyday life, Muhammadiyah community in Medan City had good financial behavior but was more influenced by habits or finance. Meanwhile, as far as Sharia finance was concerned, the Muhammadiyah community in Medan City still did not understand it.Theoretical contribution/Originality: This study provides information about the level of financial literacy and financial behavior of the Muhammadiyah community in Medan. This information becomes the basis for subsequent research to develop strategies to increase financial literacy and financial behavior of Muhammadiyah communities in Medan.Practitioner/Policy implication: Since Muhammadiyah aims to improve the welfare of the people and various studies have shown a link between the level of financial literacy and one's welfare, Muhammadiyah organizers need to pay attention to this, such as organizing a more structured and systematic program to increase Muhammadiyah citizens' knowledge of Islamic finance.Research limitation/Implication: This study still used a limited sample, namely Muhammadiyah communities. A broader sample will further confirm the validity of the literacy measurement instrument in the future.